E-273 Endovascular treatment for primary isolated distal medium vessel occlusion ischemic stroke: systematic review. (23rd July 2022) - Sequeiros, J; Rodriguez-Calienes, A; Moran-Marinos, C; Chavez, F; Alva-Diaz, C; Krishnaiah, B; Inoa, V; Hoit, D; Arthur, A; Goyal, N
Abstract : Introduction: Benefit of endovascular treatment (EVT) for distal medium vessel occlusion (dMEVO) ischemic stroke in the early time window (< 6 hours from symptoms onset) is not well established. We defined dMEVO as an isolated primary occlusion in the following arteries: segments M3-M4 in the medial cerebral artery (MCA), A2-A5 in the anterior cerebral artery (ACA), P2-P4 in the posterior cerebral artery (PCA), posterior inferior cerebellar artery (PICA), anterior inferior cerebellar artery (AICA) and superior cerebellar artery (SCA). Objective: To assess the value of EVT in dMEVO ischemic strokes. Methods: A systematic review in accordance with PRISMA guidelines was conducted. Searches were conducted using the PubMed/Medline, Scopus, Embase, and Cochrane databases up to Jan 7, 2022, including randomized clinical trials (RCT) and observational studies describing 90 days outcomes in isolated dMEVO ischemic strokes in the early time window. Our primary outcome was functional independence, defined as modified Rankin Scale score (mRS): 0–2. Secondary outcomes were 90 days mortality, intracranial hemorrhage (symptomatic and all) and excellent functional outcome (mRS 0–1). We performed a systematic review using the random effect model. Freeman-Tukey double arcsine transformation was used to stabilize the proportion variances. Heterogeneity was evaluated using the I^2 and considered high if over 50%. Results: Seventeen studies (n=527) that met the inclusion criteria were included for systematic review. Patients underwent EVT with stent-retriever (60.4%), direct aspiration (29.6%) or both (9.9%). Mean age was 69.1 years (SD=2.69), median National Institute Health stroke scale (NIHSS) was 12.46. Forty seven percent received intravenous tissue Plasminogen Activator (t-PA) and 10.68% received intraarterial t-PA. The pooled estimate of functional independence and excellent functional outcome at 90 days was achieved in 43.2% (95% IC:18.4–69.7, I2:80.7%) and 41.3% (95%IC: 27.3–56.0, I2: 75.8%) patients, respectively. Mortality at 90 days was 6.1% (95%IC:0.2–16.2, I2:64.2%). Symptomatic intracranial hemorrhage (sICH) was present in 0.9% (95%IC: 0.0–1.1, I2:0%), and all ICH was present in 5.4% (95%IC:0.1–15.1, I2: 60.1%). Conclusion: Our systematic review demonstrates decent rates of functional independence and excellent functional outcome after EVT for isolated primary dMEVO ischemic stroke in the early time window. Mortality and sICH rates were similar to EVT for proximal locations. The study is limited by high heterogenicity and unavailability of comparable medically managed patients with dMEVOs. The EVT should be directly compared with best medical treatment for dMEVOs in a large prospective randomized trial. Disclosures: J. Sequeiros: None. A. Rodriguez-Calienes: None. C. Moran-Marinos: None. F. Chavez: None. C. Alva-Diaz: None. B. Krishnaiah: None. V. Inoa: None. D. Hoit: None. A. Arthur: None. N. Goyal: None.